Mexican Origin Hispanic Men's Perspectives of Physical Activity–Related Health Behaviors. Issue 1 (February 2019) - Valdez, Luis A.; Morrill, Kristin E.; Griffith, Derek M.; Lindberg, Nangel M.; Hooker, Steven P.; Garcia, David O.
Approximately 83% of Hispanic men of Mexican origin are overweight or obese, which are both associated with increased risk of chronic disease and all-cause mortality. Consequently, men of Mexican origin have some of the highest prevalence rates of obesity-related comorbidities. Physical activity (PA) may be an important strategy for Hispanic men of Mexican origin in reducing incidence and risk factors of lifestyle diseases. The current study engaged Spanish-speaking, Hispanic men of Mexican origin aged 24–64 years with overweight/obesity to examine perspectives of health behaviors related to PA. A total of 14 in-depth semistructured individual interviews were completed between September and November of 2015 and data analyzed using an iterative deductive–inductive thematic assessment strategy. The men suggested that their PA was hindered by (a) work-related energy and time constraints, (b) socioeconomic status (SES) and the need to prioritize work, (c) adaptations to majority population lifestyle norms, and (d) perceived lack of suitable access to PA-promoting spaces. The men provided valuable insight for strategies to improve PA interventions such as (a) accurately accounting for current PA levels of participants, including occupational and transportation PA, (b) considerations of family dynamics that influence PA-based behavior change, and (c) considerations of economic and geographical constraints that can be remediated. To improve effectiveness, future PA-related intervention research with Hispanic men of Mexican origin should consider methods that (a) account for transportation and occupational PA to better tailor PA to individual needs, (b) consider sociocultural and socioeconomic influences, (c) account for social support and accountability, and (d) consider economic and geographical constraints.